SEXUALIDADE: INQUIETAÇÕES E NECESSIDADES DO ADOLESCENTE CRISTÃO SOB O ENFOQUE OPERATIVO DE PICHON-RIVIÈRE - Professiori, Neusa Maria Nimtz (2004)
The current research aims to investigate the sexuality in the adolescence, its anxiety and needs using the method of clinic investigation of psychoanalytic aproach of Enrique Pichon-Rivière, in order to obtain an understanding of the psychodynamic of the group of the adolescents with an operative emphasis . The objectives were: 1. A survey of what the adolescents think about sexuality; 2. O discuss the main conflicts lived by the adolescents in relation to the sexuality; 3. To analyze the ways of cultural manifestations of the adolescents about sexuality. The initial procedure was a bibliographic survey about the topics: sexuality, repression, unconscious fantasies and group of with operative emphasis. The adolescents of a religious community of the metropolis of São Paulo were the participants. Twelve group meetings were done with the operative emphasis using the theory and the technique of the operative groups of Enrique Pichon-Rivière. A thematic schedule was used and it provided the contents for the meetings. The topics revealed feelings and emotional reactions of the adolescents about sexuality, difficulties and facilities found in relation to the cultural manifestations and the conflicts (fear and unconscious desires) lived by the adolescents. The analyzes of the results leaded to considerations that go to two slopes: a) The anxieties represented by doubts, feelings of loss, consistent information and fears; b) The needs were represented by the loyalty, trust, social interaction, welcoming (continence) and the values of the primary (former) group of reference. Coming to a conclusion that the adolescent presents strong feelings of distrust, characterizing a constellation of fantasies the in witch the persecutory prevails, those adolescents are always preoccupied with the exterior, in what the other ones are thinking